Про роботу Південної Середньовічної експедиції у 2008 р. - Біляєва, С.О.; Болтрик, Ю.В.; Карашевич, І.В.; Фіалко, О.Є. (Археологічні дослідження в Україні, 2009)
The publication is devoted to the results of the study of mediaeval monuments of the northern Black Sea region in 2008. Permanent excavations in Ochakiv of Mykolaiv Oblast, prospecting in Beryslav Region of Kherson Oblast, and a series of works by means of non-destructive archaeology in Ackerman fortress in Bilhorod-Dnistrovskyi of Odesa Oblast have been undertaken.